Autoignition behavior and emission of biodiesel from palm oil, waste cooking oil, tyre pyrolysis oil, algae and jatropha - Nursal, Ridwan Saputra; Khalid, Amir; Abdullah, Iqbal Shahridzuan; Jaat, Norrizam; Darlis, Nofrizalidris; Koten, Hasan (Elsevier, 2021)
Alternative fuels have recently been researched on diesel substitution, with the target of reducing dependence on petroleum-based fuel in addition to reducing environmental pollution. Thanks to its regenerability and ability to absorb emissions, the opted biofuel tends to be advantageous. The present study explored the autoignition behaviour, in particular the ignition delay and process of combustion that strongly influence exhaust emissions. The analysis used biodiesel blends obtained from palm oil, waste cooking oil, algae, jatropha and tyre pyrolysis oil at various blending ratio from 2% to 20%. These blending ratios were achieved independently through a specific blending technique with pure diesel at different volumetric concentrations. The ignition delay was assessed by means of a rapid compression machine (RCM) under variant injection pressure at an elevated ambient temperature of the reaction chamber. This study discovered significant differences in ignition delays and combustion efficiency when different biodiesel blends were operated under higher injection pressures and higher ambient temperatures. The shortest ignition delay of biodiesel blend fuels is achieved at low blending concentrations, implying that lower concentrations of biodiesel encapsulate a lower fuels viscosity, preceded by excellent spray atomization, premixing, and ignitability. In addition to these implications, the shortest ignition delay was undoubtedly influenced by higher injection pressure and higher temperature conditions in which the expansion of the fuel’s molecular bound to the C–H bonding deteriorates and bonding energy dissociates. Emissions are lower than pure diesel with an increased concentration of blends; waste cooking oil-biodiesel blends experienced positive effects on the CO, HC and nitrogen oxides (NOx) via variant injection pressure; while significant improvements in HC were noticed for most fuels, corresponding to the elevated ambient temperature circumstances.